Comparison of Pneumatic Vs Holmium Yag Laser in Proximal Ureteral Stones-A Retrospective Observational Study - Sujeet Shekhar Sinha; Bhaumik B Barad; T Chadru; Kumaresan Natarajan (International Journal of Health and Clinical Research, 2021)
Introduction: Global prevalence of urolithiasis is approximately 14%, which varies depending upon age, gender, geographical location, and ethnicity.Upper urinary tract constitutes majority of stone burden, only 5% of stones are found within the bladder.Urolithiasis presents a significant economic burden on the healthcare systems across the world.Materials and Methods: A retrospective observational study was conducted at Department of Urology and Renal Transplantation, Sri Ramachandra Institute of Higher Education and Research (SRIHER), Chennai,India Demographic details of patients, history and physical examination findings, biochemical evaluation (serum creatinine, blood urea nitrogen), urinalysis, and urine culture sensitivity test results, duration of surgery, duration of hospital stay, stone migration, stone recurrence, and complication were recorded from the case files.Results: mean age of the patients in pneumatic lithotripsy group was 41.58±12.66 and in laser Lithotripsy group was 45.12±11.16. Independent-t-test was computed to find the significant mean difference between the groups. It revealed that there is no statistically significant mean difference found between the both groups regarding age. Hence both groups were similar. The mean operation time(minutes) of the patients in pneumatic lithotripsy group was 24.00±7.56 and in laser Lithotripsy group was 23.73±6.39. Independent-t-test was computed to find the significant mean difference between the groups. It revealed there is no statistically significant mean difference found between the both groups regarding operation time (minutes).Conclusion: Holmium laser is costly, less commonly available while pneumatic is cheap and widely used. Our study, establishes the supremacy of HO:YAG laser over pneumatic lithotripsy in proximal ureteric calculi and should be preferred modality, if it is available and economically feasible.